Head, Heart, and Hands : exploring art education for the individual and community - Virkkunen, Ellen (2021)
This thesis investigated the holistic education approach of ‘Head, Heart, and Hands’ and its application to art education practices. This study’s goal was to create a critical understanding of how this approach is realized and how it could be expanded through the consideration of the individual and community. The study was carried out through the interviews of five experienced art educators in the United States. The data set was analyzed using deductive and inductive thematic analysis. The findings of the study both validated and expanded upon previous un- derstandings of the Head, Heart, and Hands approach. The findings began by validating how each individual element (the Head, the Heart, and the Hands) of the approach works both individually and interconnectedly to form a holistic teaching practice. The findings then expanded on the approach through analyz- ing how the individual and community could be incorporated. This showcased how individual skills acquired through the approach can then be applied to de- veloping community and interpersonal skills. Through the analyzation of the themes and their relationships, the findings revealed how the different factors of Head, Heart, and Hands work interconnectedly alongside the individual and community to promote student engagement. When applied, this approach pro- vides opportunities for art students to be engaged in their individual and inter- personal growth through cognitive, affective, and psychomotor growth. The hope is that the findings of this study will contribute to the ongoing discussion of arts capability for education through the critical analysis of the Head, Heart, and Hands approach.